IPO Effects on Return on Assets: Evidence from Indonesian Listed Companies’ Financial Characteristics - Riyansyah Sumin; Antony; Nurni Arrina Lestari (PT. Maju Malaqbi Makkarana, 2026)
This study aims to analyze the effect of Initial Public Offering (IPO) on Return on Assets (ROA) by considering Firm Size, Liquidity, Leverage, and Tangibility in companies listed on the Indonesia Stock Exchange (IDX). The study adopts a quantitative explanatory research design using secondary data obtained from audited annual financial statements of companies that conducted IPOs during the observation period. The sample was selected using purposive sampling, while panel data were analyzed using the Fixed Effect Model (FEM) to examine the relationships among the variables. The findings indicate that IPO has a positive but insignificant effect on ROA, suggesting that additional capital raised through public offerings does not immediately improve corporate profitability. Firm Size and Leverage exhibit significant negative effects on ROA, indicating that larger firms may experience operational inefficiencies, while excessive debt increases financial burdens and reduces profitability. Conversely, Liquidity and Tangibility show positive but insignificant effects on ROA. Simultaneously, IPO, Firm Size, Liquidity, Leverage, and Tangibility significantly influence ROA, with the model explaining 59.11% of the variation in profitability. These findings imply that post-IPO financial performance depends not only on capital acquisition but also on effective asset utilization, prudent debt management, and efficient operational strategies. The study contributes to the literature on post-IPO corporate performance and provides practical insights for managers and investors in evaluating financial performance after public offerings